Arriving at a tipping point for worldwide forest decline due to accelerating climatic change - Cuauhtémoc Sáenz-Romero (The Forestry Chronicle, 2024)
The 2023–2024 El Niño is inducing an acceleration of global warming that is likely to far exceed 1.5 °C. The Boreal summer of 2023 provided numerous examples of catastrophic forest fires (e.g., >18 million hectares of forest burned in Canada, making the Canadian forest a clear carbon source rather than a carbon sink), a trend that has been accompanied by worldwide examples of unusual tree mortality linked to hotter droughts. It is reasonable to expect that the warming induced by El Niño could push forests in several parts of the world over a tipping point, where they will hardly be able to recover their original state. It is therefore necessary to address the meaning, realistically, of sustainable forest management in the era of accelerated climatic change. The ultimate goal of the broadly accepted silvicultural practice of maintaining forests in a state that resembles what we recognize as temperate or boreal forests is becoming more of an idealistic dream rather than an attainable goal. Thus, the time has arrived to discuss painful forest management decisions, such as anticipated thinning to reduce water competition and the gradual replacement of native local forest populations with more drought-resistant provenances and species.